Analysis and Compare of Cardiac Functional Efficiency Level and the Circulatory System for Short, Middle and Long-Distance Runners (Medico Legal Update, 2020)
The aims of this study are knowing of cardiac functional Efficiency level and circulatory system for theshort, middle and long -distance runner and knowing the differences of the cardia physical efficiency leveland circulatory system for the long-middle and shirt-distance runners. Thus, continuing of the sport trainingoperation may lead to take place some of the physiological changes in body, as the track and field gamesis definitely distinguished that runners. The athletes may face a various kind of functional changes resultedby various training resilience. While the Heartbeat size increases with the physical efficiency level at therelation time. Thus, we may say that physical efficiency level increases and reflects with the Heartbeatincreasing and lowering of the cardiac Heartbeat during relaxation. As the track and field races are dividingathletes into short, middle and long-distance runners. Generally, the athletes participating may face invarious games, therefore, the research importance is based on knowing the cardia physical efficiency leveland circulatory system for the short, middle long-distance runners, then attempting to know the best set infitness in raspatory circulatory system among the athletes in these activities.